Detection and correcting the wrong words from Hindi, English and Punjabi Text Documents - Shaina,; Kumar, Naresh (International Journal of Computer Sciences and Engineering, 2019)
Spell checking is a very important phase of any document processing system and Natural Language Processing. Spell Checking is a process to find the incorrect spells in a text document and to correct that particular incorrect spelling. There are various spell checking systems for various languages Like Hindi, Punjabi, English, French, Germen that can detect and correct the spell from a particular document. In this paper, we proposed a hybrid algorithm to detect and correct misspelled words from a text document written in three languages Hindi, English and Punjabi. Hybrid approach is a combination of various approaches like Dictionary lookup approach, Edit Distance Approach, Rule based approach and N-Gram approach. Proposed system can detect and correct the misspelled words from three given languages. A collision detection and correction system for alternates for misspell words has been also provided. Performance of proposed system is checked on various inputs collected from various books, websites etc. Results of the proposed system are evaluated on these outputs which have accuracy values higher than that of existing system.